صكوك الحقوق المعنوية بين النظرية والتطبيق : دراسة تحليلية في ضوء الفقه الإسلامي - سليمان، جابر موسى (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This study explores the topic of al-Huquq al-Maānawiyyah or Intangible rights, its financial values, possibility of its securitization and trading in the contemporary financial market. In view of the nature of this topic and in order to arrive at a clear understanding, this study has defined the meaning of intangible rights, its nature and position among the categories of rights. Based on this, the study starts with an introductory chapter that explains the basic concepts related to these rights, which is the main focus of this study. These concepts include the concept of money, the concept of ownership, the concept of benefits and the concept of the right. The study surveys opinions of various Muslim jurists, legal experts, economists and other experts in the field with a view to grasp these concepts and highlight their relationships among one another. The study has also highlighted the position of Muslim jurists as well as legal experts regarding the issue of intangible rights. The study has realized that the origin of the dispute in considering the financial value of these rights lies in the disagreement between the Hanafi school of law and the majority of the jurists in defining the concept of money. The point is that, the Hanafi school of law does not consider benefits and rights as money because, to them, one of the financial conditions of things is the possibility of acquisition and possession. Based on this, they have excluded benefits and rights from being considered as money. However, the majority of Muslim jurists have expanded the concept of money to include material and immaterial objects. Therefore, the study has found that the most preponderant view on this matter is that of the majority of Muslim scholars who consider these rights as money. Consequently, the study has explained the issue of securitizing these rights, analyzing its mechanisms, its processes and its Shariah guidelines. Finally, the study has conducted a practical study, with a jurisprudential analysis, of one of the issuances of the instruments of intangible rights by the SABIC company in its third issue. It thus becomes evident that the Shari'ah guidelines are not properly observed in this issuance of intangible rights